SHARI’AH ORIENTED PUBLIC POLICY ON ACEH EXPENDITURE AND DEVELOPMENT - Masthur Yahya; Muhammad Dayyan (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
This paper examines Aceh public expenditure policy in economic development especially in the area of an improvement in the living conditions of the majority of a nation’s citizens- not only in their physical well-being but also improvements in such aspects as their spiritual life, general happiness, right to be free, and the right and ability to enjoy the beauties of nature. We argue based on shari’ah oriented that public expenditure accelerates economic development by giving priorities to preserve the necessary interest that are preserved ad-dien (religion), an-nafs (life or self), al-‘aqal (intellect), an-nasb (family or progeny) and al-maal (property or wealth), the government will create a healthy conditions or environment for economic activities to achieve Islamic development goals in Aceh Province. Keyword: Public Expenditure, Shari’ah Oriented Public Policy